The relationship between a charity crowdfunding project's contents and donors' participation: An empirical study with deep learning methodologies. (May 2020) - Lee, DongIl; Park, JaeHong
Highlights: Found positive emotions depress potential donors' empathy toward the recipient and lead to little participation. Negative emotion is not effective, suggesting miserable facial emotions may not help charity crowdfunding project managers. Complex project descriptions require effort to understand the recipients' circumstances and reduce donors' participation. Our findings will also provide a useful guide when to design donation project contents given sever competition.